Under the smoke - Zorzal, Bruno (Farol, 2024)
Under the Smoke brings together a set of words arranged like a stream of consciousness poem, together with a sequence of images rephotographed from screens, where we see different volumes of smoke caused by gas bombs in demonstrations and protests. In this sense, public space stands out as a place for negotiation.